Pharmacogenomics Update in Pancreatic Cancer - Puri, Aditi; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is the fourth leading cause of cancer-related deaths in United States. Despite advances in understanding cancer biology and therapeutics, this malignancy carries a grave prognosis with a poor overall survival rate. This is especially true for patients with locally advanced and metastatic disease that are not amenable to surgical resection. Given advances in human genome sequencing and pharmacogenomics, we now better understand the complex genetic makeup of these tumors and numerous gene mutations have been identified that could be potential targets for drug development. In this review, we discuss two abstract (Abstracts #208 and #192) presented at the 2014 ASCO Gastrointestinal Cancers Symposium about pancreatic cancer genome sequencing and their implications for the future of this disease. We discuss what is known about the genome of pancreatic tumors, including common mutations like KRAS, TP53 and SMAD4, as well as discovery of additional mutations. In particular, KRAS2 mutations in a subset of patients with pancreatic cancer are discussed. While limited in size and clinical correlativity, these abstracts provide at least seven novel/targetable mutations and elucidate biologic differences in tumors with wild type and mutant KRAS. These are important steps in understanding tumor biology and genetic basis of pancreatic cancer to help develop targeted drug therapies in the fast approaching era of personalized medicine. Image: Hidalgo M. N Engl J Med 2010; 362:1605-7 (Detail of figure 1).